Computer Based Body Exposure in Adolescents With Anorexia Nervosa: A Study Protocol - Stonawski, Valeska; Sasse, Lena; Moll, Gunther; Kratz, Oliver; Horndasch, Stefanie (Frontiers in Psychiatry, 2022)
Body dissatisfaction is a core feature of eating disorders (EDs) and plays an essential role in the development and maintenance of anorexia nervosa (AN). In the current study, a computer based body exposure intervention is conducted and evaluated regarding short-term effects on body dissatisfaction, psychopathology, viewing patterns, and stress reactivity. Within a randomized controlled trial (RCT) female adolescents and young women with AN are either receiving the intervention or treatment as usual (TAU). Furthermore, in a transdiagnostic approach, a highly body-dissatisfied group of clinical control participants obtaining the intervention will be surveyed to identify AN-specific processes. The standardized four-session body exposure intervention using photographs of the own body is adapted from a manualized body image treatment program for computer use (1). Psychopathology (body dissatisfaction, body image avoidance, body checking, depression, anxiety) is assessed via standardized questionnaires before and after the intervention. During each session, attentional biases regarding one’s own body are measured via eye tracking, stress levels are measured via subjective ratings, heart rate variability, as well as salivary cortisol and alpha amylase. Between- and within-subject effects will be assessed. The pilot study aims to identify short-term effects of the intervention on body dissatisfaction and attentional bias, as well as to investigate the potential underlying mechanism of physiological habituation.